Morphometric composition analysis of Sinanodonta woodiana based on depth stratification in Tributaries Meureubo West Aceh - Heriansyah Heriansyah; Rudi Hermi; Ikhsanul Khairi; Muhammad Rizal; Akbardiansyah Akbardiansyah; Asri Mursawal; Giovani Oktavianda; Munandar Munandar; Samsul Bahri; Alfis Syharil; M Ali S (Arwana: Jurnal Ilmiah Program Studi Perairan, 2023)
Clams are aquatic biota that do not have a spine, belonging to the phylum Molluscs class Bivalvia. This study aims to determine the density, morphomteric differences of S. woodiana clams based on depth. The sampling technique used Purposive sampling method, with 1x1 meter plot and repetition 3 times. Data collection was carried out in July 2022 until completion. The results showed that the highest density of S. woodiana clams was found at a depth of 0-50 cm with an average density of 29.3 individuals/meter. Small size clams were dominantly found at a depth of 0-50 cm with a percentage reaching 97.92%, 54.46% of medium size clams were found at a depth of 50-100 cm, while 83.33% of large size clams were found at a depth of 100-150 cm. Anova test results showed significant differences with a 95% confidence interval. At a depth of 100-150 cm, the weight value of S. woodiana clams was 24.87 ± 3.36 grams, shell length 43.73 ± 1.21 cm, shell width 38.73 ± 1.76 cm, and umbo height 22.83 ± 0.76 cm. The results of this study can be concluded that the shallower the waters, the higher the density of shells, but the large size of the shells, the smaller the density.